Early infantile epileptic encephalopathy related to NECAP1: Clinical delineation of the disease and review. (9th June 2022) - Chouery, Eliane; Mehawej, Cybel; Sabbagh, Sandra; Bleik, Jamal; Megarbane, Andre
Abstract: Background and purpose: Epileptic encephalopathy (EE) refers to a heterogeneous group of epilepsy syndromes characterized by seizures as well as encephalopathies, leading to cognitive and behavioral disturbances. These conditions vary in their age at onset, their severity, and their electroencephalographic patterns. Whereas genetic factors are involved in approximately 40% of all epilepsy cases, they contribute to 80% of early infantile EEs (EIEEs), with approximately 125 genes previously linked to this disease. Methods: Whole exome sequencing (WES) was performed in a 9‐month‐old Lebanese girl presenting with EIEE. Results: WES enabled the detection of a homozygous missense mutation in the NECAP1 gene (NM_015509.3: p.Glu8Lys) in the proband. Conclusions: Here, we report the first homozygous missense mutation in the NECAP1 gene in a 9‐month‐old girl presenting with EIEE. Our findings allow a better characterization of the NECAP1 ‐linked disease and enable broadening its clinical spectrum by including, in addition to EIEE, severe generalized hypotonia, poor feeding, developmental delay, severe microcephaly, delayed myelination, abnormalities of the corpus callosum, and eye abnormalities.